Visual studies now. - Hillel, Edward (Visual Studies, 2021)
The article reports that Visual Studies can function as a counter narrative to the cloistered hierarchies and essentialism that dominate the arts and social science faculties of universities. Topics include explored strategies to construct a visual language transdisciplinary, performative, inclusive and collaborative social practice; and documentation of social media, publications, sketches and texts as well as art objects or critical discourse.